KADAR ADIPONEKTIN PLASMA PADA PASIEN YANG MENJALANI HEMODIALISIS DI RUMAH SAKIT SANGLAH DENPASAR - Sanjaya, Surya; Suwitra, Ketut (journal of internal medicine, 2010)
Adiponectin, a cytokine with anti-inß ammatory properties that is secreted from adipose tissue. Adiponectin has beenshown to be a predictor of cardiovascular events in the general population and patients who undergoing hemodialysis. The aimof this study is to evaluate serum adiponectin in patient undergoing regular hemodialysis.A cross sectional study involved 53 reguler hemodialysis patient at Sanglah hospital. Inclusion criteria was patientundergoing regular hemodialysis more than three month and twice a week. We exclude severe infections, abnormality of liverfunctions test, malignancies and diabetes mellitus.The mean of age and abdominal circumference was 48.01 ± 12.3 years old and 79.5 ± 9.99 cm. Systolic and diastolicblood pressure pre hemodyalisis was 140 ± 20.7 mmHg and 83.3 ± 10.7 mmHg. Systolic and diastolic blood pressure posthemodialysis was 148.6 ± 23.6 mmHg and 85.6 ± 11.5 mmHg, respectively. We found serum level of calcium 9.5 ± .97 mmol/l,inorganic phospat 6.4 ± 2.1 mmol/l, BUN 84.8 ± 19.9 mg/dl, serum creatinin 16.1 ± 3.9 mg/dl, hemoglobine levels 7.7 ± 1.4 g/dland blood glucose levels 92.9 ± 1.4 mg/dl. Serum levels of adiponectin was 15.4 ± 5.98 mg/l compare with normal levels 5.52mg/l. Levels of serum adiponectin in regular hemodialysis patients is three fold higher than normal population.